Imaginative Empathy in Literature: On the Theory of Presentification in Husserl and its Application in Literary Reading - Shang, Jing (Labyrinth, 2020)
This paper provides an account of the experience of empathizing with the fictional characters of literary works, through the lens of Husserl's theory of presentification. Via a critical analysis of Husserl and other phenomenologists, I argue that fictional characters, though lacking embodied presence, can be presentified to the reader in the mode of "as if." Moreover, I claim that imaginative empathy is a guided creative reproduction of sedimented past bodily experiences. This explains why, motivated by imaginative empathetic presentification, not only aesthetic feelings, but also "as if" existential feelings come to the fore. Finally, it shows to what extent presentation and the different modes of presentification are interwoven and function together.